Low-power laser irradiation (LPLI): A clinical point of view on a promising strategy to improve liver regeneration - Araújo, Tiago Gomes; Oliveira, Alexandre Gabarra [UNESP]; Teixeira, Antonio R. Franchi (Maad Rayan Publishing Company, 2018)
The capacity of the liver to regenerate is an important clinical issue after major hepatectomies and makes the difference between life and death in some cases of post-operative malfunction when the liver remnant is too small or has an impaired regenerative capacity. Several approaches have been tested to stimulate hepatic regeneration after post-operative hepatic failure syndrome; however, they have produced controversial results. A quick, simple, and harmless method that can be used intraoperatively and capable of promoting an increased regenerative capacity of the remaining liver would be very welcome. Thus, based on the data in the literature, we presented low-power laser irradiation (LPLI) as a quick, simple, and harmless method to improve liver regeneration after major hepatectomies. This article highlights the current evidence about the effects of LPLI on liver regeneration, and also suggests laser therapy as an important tool for regenerative stimulation in clinical practice.
Keywords: Clinical; Hepatectomy; Laser treatment; Liver regeneration; Liver resection; Low-power laser irradiation; LPLI